Model Misi dalam Alkitab Serta Penerapannya dalam Konteks Saat Ini - Sitompul, Baginda; Sibarani, Yosua; Siahaan, Marihot Renaldi; Siregar, Murniasi; Situmorang, Riduan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aiming to allow the understanding of mission model and its concept through literature study from the Bible and another source. The article explaining several things that first Scripture tells that mission is God heart content dan work in human history since the beginning till today. From the beginning God already has impeccable grand plan to be done by His people on earth, that had be done and be written down in the Bible.In Old Testament God send Bible figures including the Kings and Prophets, and through great event to perform His purpose on earth. Afterward in New Testament Christ send His disciples including us to spread the Gospel through great commission, that we done until now. Throughout human history, the world always changing through history in many aspects, such as social, economy, culture and mission model transform adapting the context, starting from early Christianity, middle ages, the reformation dan modern era until now the postmodern era. Implementation of mission model in the Bible can be observed through context of situation and event occurring, that can be the model of mission in present times.